The relationship between entrepreneurs’ opportunity and entrepreneurs’ growth intentions: Case of small tourism operator in Bali - Utami, Mitha Mustika Dewi; Mariana, R. Adjeng; Yazid, Mohd Faizun Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
This paper seeks to instate the role of opportunity towards the entrepreneurs’ growth intentions in the case of small tourism operator in Bali, Indonesia. The study is proposed to establish the factors of entrepreneurs’ growth intentions against the opportunity. Small tourism operator raised due to spill over demand from the high increase in traffic of tourist to Bali. Tourist come various background and culture with a various purpose of intentions. Small tourism operator was established to meet at certain level of tourist needs for a long-term benefit to the tourism industry. 112 data collected from respondent who are from the small tourism operator background. Data were collected through a questionnaire. List of 170 respondent derived from the local tourism department based on the registered members. The study revealed that opportunity is highly significant towards entrepreneurs’ growth intentions. There is a valid justification on the finding since the opportunity can help the entrepreneurs to sustain and explore potential to growth. The high motivation of entrepreneurs supported by demand from tourist will contribute to the success of entrepreneurs’ growth intentions.